The Feminization of Love and the Indwelling of God: Theological Investigations Across Indic Contexts - Barua, Ankur (Religions, 2020)
Our essay is a thematic exploration of the malleability of idioms, imageries, and affectivities of Hindu bhakti across the borderlines of certain Indic worldviews. We highlight the theological motif of the feminine-feminised quest of the seeker (virahiṇī) for her divine beloved in some Hindu expressions shaped by the paradigmatic scriptural text Bhāgavata-purāṇa and in some Punjabi Sufi articulations of the transcendent God’s innermost presence to the pilgrim self. The leitmotif that the divine reality is the “intimate stranger” who cannot be humanly grasped and who is yet already present in the recesses of the virahiṇī’s self is expressed with distinctive inflections both in bhakti-based Vedānta and in some Indo-Muslim spiritual universes. This study is also an exploration of some of the common conceptual currencies of devotional subjectivities that cannot be straightforwardly cast into the monolithic moulds of “Hindu” or “Muslim” in pre-modern South Asia. Thus, we highlight the essentially contested nature of the categories of “Hinduism” and “Indian Islam” by indicating that they should be regarded as dynamic clusters of constellated concepts whose contours have been often reshaped through concrete socio-historical contestations, borrowings, and adaptations on the fissured lands of al-Hind.